The Utilization of Yard With Longan Planting in Klambir Lima Kebun Village - Tarigan, Ruth Riah Ate; D, Ismail (Journal of Saintech Transfer, 2018)
Community service in the form of utilization of yard with longan planting was held in Klambir Lima Kebun Village from May to July 2017. The main purpose of this activity was to plant the fruit in the house yard of villagers. In addition, the specific target was to increase knowledge about the benefits of longan fruit by utilizing yard, and the expected results were the fulfilment of vitamin intake and the beautiful environment for people in the village.It is expected that the implementation of this activity would encourage villagers to utilize land around the yard of their houses. A yard in the village has not been utilized optimally to plant fruits by the villagers.Various sizes and forms of the yard can be used to plant healthy fruits, such as longan fruit. Methods used in this community service were lectures, discussions, and implementation of longan planting. The result of this activity was that the villagers planted longan seedlings in their house yard.